The effects of corporate governance on valuation of GLCs and Non-GLCs : a Singapore perspective - Tan, Dominic Hosea Kee Kuan (2017)
With an increasing focus on corporate governance practices across firms and financial markets, our paper seeks to investigate the impacts of said practices on the value of both GLCs and non-GLCs through the comparison of financial data retrieved from company annual reports and various online databases. Our study covers a total of 23 GLCs and 29 non-GLCs over a 10-year period from 2006 to 2015. Results from the correlated random effects panel regression conducted show that a firm’s Tobin’s Q is positively affected by governmental ownership. Delving deeper into the corporate governance practices, we found an inverse relationship between board size and firm valuation. On the other hand, chairman pay, board composition and number of independent directors proved to be insignificant. With our findings, we argue that having a smaller board of directors regardless of composition of independent directors is more efficient practice, while having a highly paid chairman does not necessarily lead to better company outcome as well.